Pemodelan Pengeringan Menggunakan Microwave Dengan Model Relative Energy Activation (REA) Untuk Pengeringan Kacang Hijau Berbentuk Sphere - Johannes Martua Hutagalung (Universitas Insan Cendekia Mandiri, 2022)
One of the advantages of the REA model is that the relative activation energy equation obtained from the experimental data can be used for other drying conditions with the same initial material and moisture content. Through convective data, an equation of activation energy is obtained which will be used for drying the data using a microwave. The simulation carried out is to compare the model data with experimental data of a microwave with a power of 0.25 W/g and a drying air temperature of 50 0C, then a power of 0.7 W/g and a drying temperature of 70 0C. increasing with microwave, the higher the value of the heat transfer coefficient (h) the simulation results are getting closer to the experimental data for the initial period of development, even making experimental data with increasing time.